2021
DOI: 10.3390/nano11030803
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Lactobacillus rhamnosus GG on TiO2 Nanoparticles-Induced Oxidative Stress Damage in the Liver of Young Rats

Abstract: The potential toxicity of titanium dioxide nanoparticles (TiO2 NPs) to mammals has become a widespread concern. Young individuals exposed to TiO2 NPs have a higher risk than adults. In this study, the protective effects of Lactobacillus rhamnosus GG (LGG) on liver toxicity in young rats induced by TiO2 NPs were explored. Results show that the four-week-old rats that underwent LGG after the oral intake of TiO2 NPs could prevent weight loss, reduce hematological indicators (WBC and NEUT) and serum biochemical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…All these oxidative stress and cytotoxicity markers were prevented by preincubation with BHT as an antioxidant agent for human lymphocytes. Consistent with our results, other antioxidant agents attenuated TiO 2 NPs-ROS formation and oxidative stress (Afshari-Kaveh et al, 2021; Nie et al, 2021). It has been reported that accumulation of ROS results in mitochondrial permeability transition (mPT) and mPT pore opening (Kowaltowski et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…All these oxidative stress and cytotoxicity markers were prevented by preincubation with BHT as an antioxidant agent for human lymphocytes. Consistent with our results, other antioxidant agents attenuated TiO 2 NPs-ROS formation and oxidative stress (Afshari-Kaveh et al, 2021; Nie et al, 2021). It has been reported that accumulation of ROS results in mitochondrial permeability transition (mPT) and mPT pore opening (Kowaltowski et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that TiO 2 is allowed to be added to animal feed additives in China, so in the process of feeding mice, TiO 2 was ingested and accumulated in the body, resulting in a certain amount of Ti in mouse liver in Control group. Ti contents in the liver of mice exposed to TiO 2 NPs was only twice that of Control group, which is regarded as a normal phenomenon, and in our preliminary laboratory studies have also indicated similar experimental results 51 …”
Section: Discussionsupporting
confidence: 80%
“…LGG is a natural and commercial probiotic with excellent anti-inflammation and antioxidation functions . Numerous researchers used LGG to treat inflammation-induced organs or tissues damage. , In our previous work, we explored the protective effect of LGG on TiO 2 NPs-induced liver and intestine inflammation injury in juvenile rats. , Therefore, we supplemented MetS mice with LGG to protect against fructose and TiO 2 NPs-caused liver and colon damage. After the treatment with LGG, the TiO 2 NPs-induced excessive inflammation factors were reduced, and the increase in gut permeability was effectively prevented, which can explain the decreased feces and serum LPS level (Figure ).…”
Section: Discussionmentioning
confidence: 99%